Uncertainty and effectiveness of control with gage in the sugar industry - Cabrera Delgado, Erenia; Coello Machado, Norge Isaías; Toscano Alfonso, Juan Manuel (Centro Azúcar Journal, 2008)
The investigations express the relation between geometry aspects and statistical parameters of dimensional control in the manufacturing process. It defines the errors in the dimensional control with smooth limit gage as error type I and error type II and the effectiveness of the dimensional control with calibre through the procedures developed for the calculation of error and effectiveness. An analysis of the norm NC 16-04 to calculate the geometric parameter with the smooth limit gage on the base of effectiveness and it is offered some recommendations to diminish the instability of errors and to increase the effectiveness. This process are very used the mechanic and sugar industry.